Assessment of two herbicide wiping devices - Harrington, K.C.; Hood, M.Z.; McKinnon, K.C. (New Zealand Plant Protection, 2000)
If herbicides were wiped on to weeds rather than sprayed the risk of spray drift would be eliminated Two devices designed to apply herbicides using rolling wipers were assessed for their ability to apply constant amounts of herbicide to treated surfaces The Weed Ball Applicator treated strips only 36 mm wide despite having a roller 100 mm wide whereas the Turf Girl applicator delivered a 500 mm wide band Both applicators suffered from a tendency to apply less herbicide as the herbicide reservoir emptied with the nearly empty Weed Ball delivering only 124 of that applied when full Adjustments to the flow rate as the reservoir emptied could be made using a tap in both devices A field evaluation of the Weed Ball applicator on dichondra showed that it had good potential for selective localized applications of herbicides to lawn weeds Of the treatments evaluated a metsulfuron solution (045 g/litre) gave the best control